PEACE INSPIRED BY CONSCIENCE: PRAYER, MARTIAL ARTS, AND QIGONG AS CULTURAL PRACTICES IN A GLOBALIZED WORLD (Религиски дијалог и соработка, 2025)
Globalization has accelerated cultural exchange but also intensified competition, fuelingwars, climate crises, disasters, and cyber threats that heighten global anxiety. In response, thispaper explores conscience-centered peace practices rooted in Tai Ji Men, a qigong and martial artsMenpai with a long tradition of spiritual cultivation. Drawing from over two decades of personalpractice, the study highlights how prayer, martial arts, and qigong can foster inner calmness,moral action, and collective resilience. Special attention is given to the Bell of World Peace andLove, a global cultural initiative through which world leaders have pledged to uphold conscienceand harmony. The paper also examines the Tai Ji Men case, a prolonged legal and human rightscontroversy in Taiwan, as a litmus test for freedom of belief and cultural diversity. Through analysisof lived experience, international engagement, and the broader human rights discourse, thestudy argues that conscience awakening and cultural-spiritual practices can generate nonviolent,resilient forces for peace. Ultimately, resolving structural injustices such as the Tai Ji Men case is essentialnot only for Taiwan’s democratic development but also for strengthening global solidarityand advancing sustainable peace.”